2020
DOI: 10.7717/peerj.8553
|View full text |Cite
|
Sign up to set email alerts
|

Implicit motor imagery performance is impaired in people with chronic, but not acute, neck pain

Abstract: Background People with chronic neck pain have impaired proprioception (i.e., sense of neck position). It is unclear whether this impairment involves disruptions to the proprioceptive representation in the brain, peripheral factors, or both. Implicit motor imagery tasks, namely left/right judgements of body parts, assess the integrity of the proprioceptive represention. Previous studies evaluating left/right neck judgements in people with neck pain are conflicting. We conducted a large online study to comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…The order of applications was organized according to the random number. The software was set in the “vanilla” mode with 40 images and 5 s of display time for each image ( Wallwork et al, 2020 ). The participant was asked to sit on a stool, and the iPad was placed on the table.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The order of applications was organized according to the random number. The software was set in the “vanilla” mode with 40 images and 5 s of display time for each image ( Wallwork et al, 2020 ). The participant was asked to sit on a stool, and the iPad was placed on the table.…”
Section: Methodsmentioning
confidence: 99%
“…Hand and foot LRJTs were performed to evaluate upper and lower limb body representation; currently, various body part discrimination tests—such as shoulder, knee, and movement direction of the neck and back—are available ( Breckenridge et al, 2019 ). The assessment ability of LRJT depends on the affected body part; for example, the hand LRJT was not disrupted in participants with neck pain ( Wallwork et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were conducted in patients with upper limb pain [37][38][39][40][41][42][43][44], including frozen shoulder, hand OA, carpal tunnel syndrome, wrist pain and lateral epicondylitis. The performance of the LRJT in patients with low limb pain [45][46][47][48], fibromyalgia [49] back and neck pain [50][51][52][53], and facial pain [54] was also investigated. Except for two populations with tendinopathies [44,46], the integrity of body schema was distorted in populations with limb and facial pain.…”
Section: ) Somatosensory Information (1) Proprioceptive Informationmentioning
confidence: 99%
“…Previous research has demonstrated that chronic neck pain and subclinical recurrent neck pain (SCNP) alter afferent input from the neck and impact many cortical processes including proprioception [1,[10][11][12], sensorimotor integration (SMI) [13,14], and multisensory integration [15,16]. When comparing the effects of SCNP on head, shoulder, trunk and whole body positions during active and passive movement of the right shoulder, Paulus and Brumagne found significant differences in head movements between groups suggesting inconsistencies in reference frame selection [1].…”
Section: Introductionmentioning
confidence: 99%